In Vitro Assessment of Clevidipine Using the Profilin1 Hypertensive Mouse Model - Hamdy H. Hassanain; Mohamed D. H. Hassona; Erika G. Puente; Chengwen Sun; Zeinb A. Abouelnaga; David B. Tulman; Sergio D. Bergese (MDPI AG, 2013)
Hypertension represents a major risk factor for cardiovascular events, associating with vascular hypertrophy and dysfunction in resistance vessels. Clevidipine is a novel antihypertensive drug working as a selective calcium channel antagonist with an ultra-short half-life that lowers arterial blood pressure by reducing systemic arterial resistance. The aim was to assess the effect of clevidipine on the hypertrophic vessels of profilin1 hypertensive transgenic mice compared to sodium nitroprusside (SNP) and labetalol using wire myograph techniques. The effects of clevidipine, SNP and labetalol on the hypertrophic vessels were studied on mesenteric arterial function from 8 profilin1 hypertrophic mice and eight non-transgenic controls. Our results showed a significant difference between the effects of the three drugs on the hypertrophic mesenteric arteries of transgenic profilin1 mice compared to the non-transgenic controls. The half maximal effective concentration (EC50) of clevidipine, SNP and labetalol in profilin1 mice (1.90 ± 0.05, 0.97 ± 0.07, 2.80 ± 0.05 nM, respectively) were significantly higher than the EC50 in non-transgenic controls (0.91 ± 0.06, 0.32 ± 0.06, 0.80 ± 0.09 nM, respectively). Moreover, the increase in the EC50 for clevidipine (2-fold) to produce the same effect on both normal and hypertrophic arteries was less than that of SNP (3-fold) and labetalol (3.5-fold). Therefore, we concluded clevidipine exhibited the lowest dose shift to relax the hypertrophic vessels compared to SNP and labetalol in the profilin1 hypertrophic animal mouse model.